2008
DOI: 10.1371/journal.pbio.0060062
|View full text |Cite
|
Sign up to set email alerts
|

Social Context–Induced Song Variation Affects Female Behavior and Gene Expression

Abstract: Social cues modulate the performance of communicative behaviors in a range of species, including humans, and such changes can make the communication signal more salient. In songbirds, males use song to attract females, and song organization can differ depending on the audience to which a male sings. For example, male zebra finches (Taeniopygia guttata) change their songs in subtle ways when singing to a female (directed song) compared with when they sing in isolation (undirected song), and some of these change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
291
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(302 citation statements)
references
References 74 publications
(126 reference statements)
10
291
1
Order By: Relevance
“…Studies of activity-dependent gene induction, such as expression of immediate-early genes (IEGs), demonstrate that the NCM and CMM exhibit specific neural responses to conspecific songs as opposed to heterospecific songs in both parental (Mello et al, 1992) and brood parasitic songbirds (Louder et al, 2016), attractive conspecific songs as opposed to less attractive songs (Leitner et al, 2005;Monbureau et al, 2015), recently experienced songs as opposed to novel songs (Sockman et al, 2002), songs that include the birds' local dialect as opposed to a foreign dialect (Maney et al, 2003), as well as non-learned calls versus silence (Gobes et al, 2009). The NCM and CMM also play distinct roles in song recognition, as some songbirds exhibit greater IEG induction in the CMM in response to preferred song, whereas IEG induction in the NCM reflects song familiarity (Woolley and Doupe, 2008). Thus, the NCM and CMM have emerged as key brain regions for social recognition of acoustic cues in many species of parental and parasitic oscine birds.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of activity-dependent gene induction, such as expression of immediate-early genes (IEGs), demonstrate that the NCM and CMM exhibit specific neural responses to conspecific songs as opposed to heterospecific songs in both parental (Mello et al, 1992) and brood parasitic songbirds (Louder et al, 2016), attractive conspecific songs as opposed to less attractive songs (Leitner et al, 2005;Monbureau et al, 2015), recently experienced songs as opposed to novel songs (Sockman et al, 2002), songs that include the birds' local dialect as opposed to a foreign dialect (Maney et al, 2003), as well as non-learned calls versus silence (Gobes et al, 2009). The NCM and CMM also play distinct roles in song recognition, as some songbirds exhibit greater IEG induction in the CMM in response to preferred song, whereas IEG induction in the NCM reflects song familiarity (Woolley and Doupe, 2008). Thus, the NCM and CMM have emerged as key brain regions for social recognition of acoustic cues in many species of parental and parasitic oscine birds.…”
Section: Introductionmentioning
confidence: 99%
“…Habituation is not simply the loss of all neural responses to the auditory stimulus, as neurons in the auditory forebrain still fire in response to the familiar song (albeit at a somewhat lower rate compared to when the song is first novel) (9-11). These changing neural responses may be related to shifts in how the singer is perceived in the context of territorial and colonial social life (3,12,13).Studies of song response habituation have focused on a single gene, ZENK. However, other genes are likely to be involved as well, as studies in other systems have indicated that experience can affect the expression of many genes in the brain (e.g., refs.…”
mentioning
confidence: 99%
“…The work of Allison Doupe and her colleagues has beautifully illustrated the role of social contexts on vocal learning in the zebra finch (Woolley and Doupe 2008;Kojima and Doupe 2011). Moreover, studies on the zebra finch have also shown that motor learning occurs earlier and is more sophisticated than previously thought (Raghav and Doupe 2013).…”
Section: Neurobiological Foundations Of Social Learningmentioning
confidence: 98%